2014
DOI: 10.1089/ars.2013.5593
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chelatable Iron as a Therapeutic Modality in Parkinson's Disease

Abstract: The therapeutic features of a chelation modality established in translational models and in pilot clinical trials warrant comprehensive evaluation of symptomatic and/or disease-modifying potential of chelation in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
470
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 517 publications
(511 citation statements)
references
References 73 publications
13
470
0
8
Order By: Relevance
“…A direct relationship between total iron (in the plasma) and labile iron pool (in the cells) is evident in experimental or clinical systemic iron overload, where the benefits obtained with a cell-permeant iron chelator confirm the pathological relevance of non-ferritin bound iron (Pennell et al 2011). Even though the generating mechanisms of brain siderosis are different, the same setting may be found in it, as suggested by the promising results obtained by targeting chelatable iron with deferiprone in an experimental model of PD and in early-stage PD patients (Devos et al 2014). Important aspects in this possible pathogenic mechanisms are not clear yet; in particular, what is the difference between iron accumulation in normal ageing and in neurodegenerative disorders with brain iron overload?…”
Section: Ferritin In Brain Disorders With Altered Iron Homeostasismentioning
confidence: 94%
“…A direct relationship between total iron (in the plasma) and labile iron pool (in the cells) is evident in experimental or clinical systemic iron overload, where the benefits obtained with a cell-permeant iron chelator confirm the pathological relevance of non-ferritin bound iron (Pennell et al 2011). Even though the generating mechanisms of brain siderosis are different, the same setting may be found in it, as suggested by the promising results obtained by targeting chelatable iron with deferiprone in an experimental model of PD and in early-stage PD patients (Devos et al 2014). Important aspects in this possible pathogenic mechanisms are not clear yet; in particular, what is the difference between iron accumulation in normal ageing and in neurodegenerative disorders with brain iron overload?…”
Section: Ferritin In Brain Disorders With Altered Iron Homeostasismentioning
confidence: 94%
“…This encouraging trial data has not led to further AD clinical development of compounds that target iron. However, a recent Parkinson's disease clinical trial of the iron chelator, deferiprone, showed improvement in motor function over an 18-month period [222].…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…Results indicated that the early start group (who started deferiprone six months earlier) had a slower disease progression on the 18 month-follow up visit as documented by a 2.4 points lower motor score in the Unified PD Rating Scale (UPDRS-III). Additionally, iron content in the SN, as well as malonaldehyde, carbonyl-proteins and 8-oxdG in the CSF were significantly decreased compared to baseline [134]. Patients with lower ceruloplasmin activity in the CSF appeared to respond better to iron chelation suggesting that ceruloplasmin may modify the response to deferiprone treatment in PD [135].…”
Section: Parkinson's and Alzheimer's Diseasesmentioning
confidence: 89%